The Change of Nutrients in Tidal Swamp Soil and Palm Oil Plant Due to Several Dosages of Application of Palm Oil Mill Effluent on Planting Media - Bakri; Siti Masreah Bernas; Dedik Budianta; Muhammad Said (Sains Tanah: Journal of Soil Science and Agroclimatology, 2015)
The change of several soil nutrients in tidal swamp area due to addition of palm oil mill effluent (POME) on soil media. The research objective was to determine the effect of different dosages application of palm oil mill effluent on nutrient changes within planting media. This experiment was conducted in a plastic house by using 8 month ages of plants consisting of 9 pots combined with 6 levels of BOD treatment (Biological Oxygen Demand) concentrations as follows: 20.000 mg/l (L5), 15.000 mg/l (L4), 10.000 mg/l(L3), 5.000 mg/l (L2), 2.500 mg/l (L1) and water only (Lo). The plants were grown for six months from December 2014 to June 2015. The variables observed were pH (H2O), pH KCl, C-Organic, N-Total, P-Bray I (ppm), K- dd, Na, Ca, Mg, Cation Exchange Capacity, Al-dd and H-dd as well as N, P and K nutrients of crop tissues. The results showed that addition of palm oil mill effluent increased soil pH and availability of soil N, P, K, Ca and Mg. Meanwhile nutrients content of N, P and K in tissues were not increased significantly by given POME with BOD up to 20.000 mg/l.